Preparation method of marble tile with stone luster and marble tile

Through inkjet printing and glazing technology, the ink discharge phenomenon is formed under the glaze layer, which solves the problem of poor authenticity of marble tiles and stone, and achieves the effects of high transparency, moist touch and stone gloss.

CN119638492AActive Publication Date: 2025-03-18DONGGUAN CITY WONDERFUL CERAMICS IND PARK +1
View PDF 4 Cites 0 Cited by

Patent Information

Application Number
CN202411902332.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-03-18
Estimated Expiration
2044-12-23

AI Technical Summary

Technical Problem

The existing marble tiles are depressed on the surface of the glaze layer, resulting in a visual difference from the real stone, which has a poor sense of reality.

Method used

By inkjet printing the stone texture pattern on the ceramic body, the superposition of matte finely engraved digital ink and high-temperature matte white ink is combined with the surface glaze to form an ink discharge phenomenon, covering it under the glaze layer, achieving a recessed surface from the inside to the outside.

Benefits of technology

It has achieved the realization of the stone of marble tiles, with clear transparency and close to the touch of real stone, visually hydrated and greasy, and reduced the consumption of raw materials and fuel.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119638492A_ABST
    Figure CN119638492A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of a marble tile with stone gloss and the marble tile, and the method comprises the following steps: carrying out ink-jet printing on a ceramic green body applied with ground glaze according to a stone texture pattern obtained in advance to obtain a pattern decoration layer, ink used during ink-jet printing comprises matte engraving digital ink and high-temperature matte white ink. Applying cover glaze on the pattern decoration layer to enable the cover glaze and the pattern decoration layer to form an ink discharge phenomenon, and covering the ink discharge phenomenon under a glaze layer formed by the cover glaze; and treating the ceramic body applied with the cover glaze into the marble ceramic tile with stone luster. According to the invention, the two kinds of digital ink, namely the matte engraving digital ink and the high-temperature matte white ink, are superposed, and the ink performance after glazing is combined with the glaze slip performance, so that an ink discharge phenomenon is formed, the ink discharge reaction occurs below a glaze layer, and then a surface depression feeling from inside to outside is generated after glazing; and the effect of precipitation erosion on the surface of the real stone can be achieved visually.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of ceramics, and in particular to a method for preparing a marble tile with stone luster and the marble tile. Background Art

[0002] In order to increase the realism of the stone, the current marble tiles are all recessed on the upper layer of the marble tile glaze layer to form a visual effect closer to the real stone. However, since the existing marble tiles are only recessed on the surface of the glaze layer, the recessed texture is usually shallow, which has a certain visual difference from the deep texture from the inside to the outside of the real stone, resulting in poor stone realism of the marble tiles.

[0003] Therefore, the prior art has defects and needs to be improved and developed. Summary of the invention

[0004] The technical problem to be solved by the present invention is that, in view of the above-mentioned defects of the prior art, a method for preparing marble tiles and marble tiles with stone luster are provided, aiming to solve the problem that in the prior art, marble tiles are recessed on the surface of the glaze layer, which still has a certain visual difference from the real stone, resulting in poor stone reality of the marble tiles.

[0005] The technical solution adopted by the present invention to solve the technical problem is as follows:

[0006] The first aspect of the present application provides a method for preparing a marble tile with stone luster, which comprises:

[0007] Inkjet printing is performed on the ceramic body to which the base glaze has been applied according to the pre-acquired stone texture pattern to obtain a pattern decoration layer, wherein the ink used in the inkjet printing includes matte fine carving digital ink and high-temperature matte white ink;

[0008] Applying a top glaze on the pattern decoration layer, so that the top glaze and the pattern decoration layer form an ink drainage phenomenon, and the ink drainage phenomenon is covered under the glaze layer formed by the top glaze;

[0009] The ceramic body to which the glaze has been applied is treated as a marble tile with a stone luster.

[0010] According to the above-mentioned technical means, the embodiment of the present application utilizes the superposition of two digital inks, matte carving digital ink and high-temperature matte white ink, and combines the ink performance after glazing with the glaze slurry performance to form an ink drainage phenomenon. The ink drainage reaction occurs under the glaze layer, and then produces a surface depression from the inside to the outside after glazing, which can visually achieve the effect of precipitation erosion on the surface of real stone.

[0011] In one embodiment of the present application, the step of obtaining the stone texture pattern includes:

[0012] The surface of the target stone is scanned by a scanning device with a resolution of 3200 dpi to obtain an original scanned image, and the original scanned image is used as a stone texture pattern.

[0013] According to the above technical means, the embodiment of the present application uses various real stones as materials and adopts a scanning device with a resolution of 3200dpi to scan all the information on the surface of the target stone, and 100% of the texture information of the stone itself is retained.

[0014] In one embodiment of the present application, a glaze is applied on the pattern decoration layer so that the glaze and the pattern decoration layer form an ink drainage phenomenon, and the ink drainage phenomenon is covered under the glaze layer formed by the glaze, including:

[0015] Using a swing-type pressure glaze spraying cabinet to apply a top glaze on the pattern decoration layer, so that the top glaze and the pattern decoration layer form an ink drainage phenomenon, and the ink drainage phenomenon is covered under the glaze layer formed by the top glaze;

[0016] Among them, the pressure control of the swing pressure glaze spraying cabinet is 1-1.2MPa, the glazing specific gravity is 1.38-1.40, and the glazing amount is 130-190g / m 2 .

[0017] According to the above technical means, the embodiment of the present application uses a swing-type pressure glaze spraying cabinet to apply the top glaze. The spray gun of the swing-type pressure glaze spraying cabinet can swing back and forth, so that the sprayed top glaze is naturally accumulated and superimposed, so that the ink and the top glaze are combined to produce accumulated crystals during firing. Since the ink discharge reaction occurs under the glaze layer, this process will produce a surface concave feeling from the inside to the outside after glazing.

[0018] In one embodiment of the present application, the chemical components of the glaze, measured by mass percentage, include:

[0019] SiO2 50-54%, Al2O3 17-22%, CaO 5-8%, MgO 1-3%, Ka2O 4-6%, Na2O2-4%, ZnO5-8%, BaO 7-11%, SrO 2-4%.

[0020] According to the above-mentioned technical means, the embodiment of the present application adopts a glaze with high hardness and high transparency, which improves the transparency and hardness of the product after later polishing.

[0021] In one embodiment of the present application, a ceramic body to which a glaze has been applied is processed into a marble tile having a stone luster, comprising:

[0022] The ceramic body to which the glaze has been applied is fired at a firing temperature of 1130 to 1230° C. and a firing time of 60 to 90 minutes to obtain a fired semi-finished product;

[0023] Use polishing equipment to glaze the fired semi-finished products;

[0024] The fired semi-finished product after glazing is waxed to obtain marble tiles with stone luster.

[0025] According to the above technical means, the firing process of the embodiment of the present application can form a good combination between the glaze and the ceramic body, and enhance the overall stability; polishing can remove tiny flaws on the glaze surface, making it smoother and brighter. The polished glaze has a stone-like luster, which improves the visual effect of ceramic products; the polished glaze forms a hard protective layer, which enhances the wear resistance; the polished glaze is smoother and less likely to absorb dirt and dust. Waxing can form a protective film on the glaze surface to prevent the glaze from being worn and contaminated, and can maintain the gloss of the glaze.

[0026] In one embodiment of the present application, glazing the fired semi-finished product using a polishing device includes:

[0027] The first glaze polishing is performed using a 600-mesh elastic grinding block, an 800-mesh elastic grinding block and a resin brush on the first polishing device;

[0028] Use the 800-mesh elastic grinding block on the second polishing equipment to perform the second glaze polishing;

[0029] Use the resin brush on the third polishing device and the 800-mesh elastic grinding block to perform the third glaze polishing;

[0030] The fourth glaze polishing is performed using a 1000-mesh elastic grinding block, a 1500-mesh elastic grinding block, a 2000-mesh elastic grinding block and a 3000-mesh elastic grinding block on the fourth polishing equipment.

[0031] According to the above-mentioned technical means, the glaze polishing process of the embodiment of the present application is a rough polishing using the superposition of elastic bright polishing blocks and resin brushes, so as to achieve the effect of cutting and repairing the glaze polishing marks on the glaze surface, reduce fiber marks on the glaze surface, increase the smoothness of the glaze surface, and thus improve the light refractive index of the product and increase the transparency and clarity of the product.

[0032] In one embodiment of the present application, the chemical components of the elastic grinding block and the resin brush, measured by mass percentage, both include:

[0033] Phenolic resin powder 35-45%, diamond powder 15-20%, corundum powder 5-10%, green silicon carbide powder 5-10%, zinc oxide powder 10-15%, cerium oxide powder 15-20%, titanium salt 4-6%, zinc stearate 2-4% 。

[0034] The elastic grinding block and the resin brush in the embodiment of the present application have the same chemical composition, and the fiber scratches generated during the grinding process are similar in depth. The high-purity resin fiber brush fills and repairs the fiber scratches, while increasing the flatness of the surface layer, reducing the light scattering rate, and improving the transmittance, achieving the effects of clear transparency, comfortable gloss, and smooth feel.

[0035] In one embodiment of the present application, waxing is performed on the fired semi-finished product after glazing to obtain a marble tile with a stone luster, comprising:

[0036] The fired semi-finished product after glazing is waxed twice with the same wax water to obtain marble tiles with stone luster;

[0037] Among them, the wax water used for waxing includes: high permeability small molecular weight modified silicone, medium molecular weight modified silicone, large molecular weight modified silicone, environmentally friendly solvent oil and high-efficiency organic tin curing agent.

[0038] According to the above-mentioned technical means, the embodiment of the present application performs waxing twice, which can maintain the moisture of the marble tile surface, thereby improving the durability of the product; and, after use and wear, there will be no defects of reflection and large gloss contrast in frequently worn parts.

[0039] A second aspect of the present application provides a marble tile, wherein the marble tile is prepared by the method for preparing a marble tile with stone luster as described above.

[0040] In one embodiment of the present application, the thickness of the marble tile is 9 mm, and the glossiness of the marble tile is 65-70 degrees.

[0041] This application has the following beneficial effects:

[0042] First, the embodiment of the present application utilizes the superposition of two digital inks, matte carving digital ink and high-temperature matte white ink, and combines the ink performance after glazing with the glaze slurry performance to form an ink drainage phenomenon. The ink drainage reaction occurs under the glaze layer, and then after glazing, a surface depression feeling from the inside to the outside is produced, which can visually achieve the effect of precipitation erosion on the surface of real stone.

[0043] Second, the marble tiles prepared in the embodiments of the present application have a clear sense of transparency, a touch close to that of real stone, and a visually moist and oily feel.

[0044] Third, the embodiment of the present application utilizes the superposition of two digital inks, matte carving digital ink and high-temperature matte white ink, to reproduce the fine stone grain texture that has grown naturally over thousands of years. The fineness of the stone grain line reaches 0.1mm, making the marble tiles more realistic.

[0045] Fourth, the 9 mm thick marble tiles produced in the embodiment of the present application reduce the consumption of raw materials and fuel. BRIEF DESCRIPTION OF THE DRAWINGS

[0046] Figure 1 The present invention is a flow chart of a preferred embodiment of a method for preparing marble tiles with stone luster.

[0047] Figure 2 , Figure 3 and Figure 4 All of them are schematic diagrams of the effects of marble tiles prepared by the present invention. DETAILED DESCRIPTION

[0048] In order to make the purpose, technical solution and advantages of the present invention clearer and more specific, the present invention is further described in detail below with reference to the accompanying drawings and examples. It should be understood that the specific embodiments described herein are only used to explain the present invention and are not used to limit the present invention.

[0049] The gloss of marble stones on the market varies, and the gloss changes greatly after use, and the anti-fouling effect is poor. The gloss of existing marble tiles is generally around 20 degrees, 40 degrees, 60 degrees, and 90 degrees, and the thickness is generally 12mm. Compared with real stone, these glosses have a certain degree of distortion. Marble tiles with a glossiness below 80 degrees have insufficient product clarity, weak detail levels, poor transparency, and rough stone lines. High-gloss marble tiles with a glossiness of 90 degrees will make the product surface like a mirror, lose the moist and greasy feeling of the stone itself, and the product feel is insufficient. At the same time, the product structure prepared by the previous preparation process is single, the surface effect is quite different from the real stone, the product thickness is thick, and the processing is difficult, which in turn leads to restrictions on its use in the construction and decoration industries.

[0050] The marble tiles provided by the present application have the colorful colors of the stone itself, beautiful and natural textures, and the texture of the stone is close to the stone itself, especially the jade-like series and the stone after the natural extrusion fault. The product prepared according to the process of the embodiment of the present application can eliminate the smaller impurities and defects of the stone itself, retain the fine texture of the original natural growth inside the stone, and at the same time have high transparency and the water-wetting and oiliness of the stone itself.

[0051] The following describes the method for preparing marble tiles with stone luster according to an embodiment of the present application with reference to the accompanying drawings. In view of the problem that in the prior art mentioned in the above background technology, marble tiles are recessed on the surface of the glaze layer, which still has a certain visual difference from the real stone, resulting in poor stone reality of the marble tiles, the present application provides a method for preparing marble tiles with stone luster, in which a ceramic blank to which a base glaze has been applied is inkjet printed according to a pre-acquired stone texture pattern to obtain a pattern decoration layer, wherein the ink used in inkjet printing includes matte fine carving digital ink and high-temperature matte white ink; a top glaze is applied on the pattern decoration layer so that the top glaze and the pattern decoration layer form an ink drainage phenomenon, and the ink drainage phenomenon is covered under the glaze layer formed by the top glaze; the ceramic blank to which the top glaze has been applied is processed into a marble tile with stone luster. The present invention utilizes the superposition of two digital inks, matte carving digital ink and high-temperature matte white ink, and combines the ink performance with the glaze slurry performance after glazing to form an ink drainage phenomenon. The ink drainage reaction occurs under the glaze layer, and then produces a surface depression from the inside to the outside after glazing, which can visually achieve the effect of precipitation erosion on the surface of real stone.

[0052] The present invention provides a method for preparing marble tiles with stone luster, such as Figure 1 As shown, the method for preparing marble tiles with stone luster comprises:

[0053] Step S100, inkjet printing is performed on the ceramic body to which the base glaze has been applied according to the pre-acquired stone texture pattern to obtain a pattern decoration layer, wherein the ink used in the inkjet printing includes matte fine carving digital ink and high-temperature matte white ink.

[0054] Specifically, the digital ink obtained by superimposing matte engraving digital ink and high-temperature matte white ink according to different grayscales has oiliness and wateriness. Among them, the grayscale range is 1 to 100. When using matte engraving ink, it is necessary to adapt to the kiln firing temperature. The same ink fired in different kilns will have some shiny, and some poor engraving effects and not fine enough. Therefore, the ink formula needs to be adjusted according to the actual situation.

[0055] In the embodiment of the present application, the glaze is sprayed before the ink is completely dry. Before spraying the glaze, it passes through a drying kiln of about 20 meters and is dried at 80-120°C for 1.5-2 minutes. The high temperature evaporates the moisture on the surface layer of the ink, retaining the oiliness of the surface carved ink. When spraying the glaze, the water-based characteristics of the glaze and the oily characteristics of the ink, as well as the incompatibility of water and oil, are used to spray the glaze on layer by layer until the glaze is completely covered and flat. During the initial contact between the glaze and the ink, that is, the middle layer below the surface of the glaze and above the surface of the ink forms a physical ink drainage phenomenon, achieving a stone grain effect generated from the inside. Conventional marble tiles do not superimpose matte carved digital ink and high-temperature matte white ink, nor do they have professional and refined operations. Traditional marble is generally produced using an inkjet combined with a flatbed printing process. After the glaze is applied, the glaze and ink cannot physically drain ink.

[0056] The embodiment of the present application utilizes the superposition of different grayscale texture information of two digital inks, matte precision carving digital ink and high-temperature matte white ink, and adopts the water-based characteristics of the glaze and the oil-based characteristics of the ink. It utilizes the incompatibility of water and oil under the glaze layer to achieve a slightly differentiated ink discharge effect with different depths. After glazing, the fine stone grain texture of the stone itself that has grown naturally for thousands of years is reproduced, and the fineness of the stone grain line reaches 0.1mm, making the marble tiles more realistic.

[0057] In the embodiment of the present application, the step of obtaining the stone texture pattern includes:

[0058] The surface of the target stone is scanned by a scanning device with a resolution of 3200 dpi to obtain an original scanned image, and the original scanned image is used as a stone texture pattern.

[0059] Specifically, the embodiment of the present application uses various real stones as materials and adopts a scanning device with a resolution of 3200dpi to scan all the information on the surface of the target stone, thereby retaining 100% of the texture information of the stone itself.

[0060] In addition, the embodiment of the present application uses the original scanned image as a stone texture pattern. In order to avoid slow response, jamming, low efficiency, etc. of the file during the design process, conventional files are usually converted by reducing the file clarity to improve work efficiency without affecting inkjet printing. For example, the same design file has an original material size of 2GB. Because the file content is rich and the file is large, during the design process, the design computer processes the file slowly. Without affecting the clear view of the product color 1 meter away, the operation of reducing the file resolution was chosen to reduce the file to 360dpi, or 300dpi, doubling the file processing speed. For the same file pattern, through operation conversion, reducing detail differentiation and other adjustments, the file information value is reduced, resulting in the final designed file being only 10 to 15G. The file size can reflect the richness and details of the file content. The embodiment of the present application uses a high-resolution scanning device to scan the surface of the target stone and retains the original scanned image, so as to obtain a stone texture pattern with rich details, thereby eliminating small impurity defects contained in the stone itself, improving the natural beauty, and also being able to design the direction of the stone grain line and the overlap of the stone grain according to the texture of the stone itself, so that the error of the fineness of the produced stone grain line is ≤1 pixel.

[0061] like Figure 1 As shown, the method for preparing marble tiles with stone luster also includes:

[0062] Step S200: applying a top glaze on the pattern decoration layer, so that the top glaze and the pattern decoration layer form an ink drainage phenomenon, and the ink drainage phenomenon covers the glaze layer formed by the top glaze.

[0063] In one embodiment of the present application, step S200 specifically includes: applying a top glaze on the pattern decoration layer using a swing-type pressure glaze spraying cabinet, so that the top glaze and the pattern decoration layer form an ink discharge phenomenon, and the ink discharge phenomenon is covered under the glaze layer formed by the top glaze; wherein the pressure of the swing-type pressure glaze spraying cabinet is controlled to be 1-1.2MPa, the glazing specific gravity is 1.38-1.40, and the glazing amount is 130-190g / m 2 .

[0064] Specifically, the glaze of the embodiment of the present application adopts a swinging pressure glaze spraying cabinet, which uses 6 to 8 spray guns to swing back and forth, with a pressure of 1 to 1.2 MPa, to ensure that the ink discharge reaction of the digital ink and the glaze is covered under the glaze layer in a uniform state. The spray gun of the swinging pressure glaze spraying cabinet can swing back and forth, so that the sprayed glaze is naturally accumulated and superimposed, and then the ink and the glaze are combined during firing to produce accumulated crystals. Since the ink discharge reaction occurs under the glaze layer, this process will produce a sense of surface depression from the inside to the outside after glazing. The surface of conventional marble tiles is all concave in the upper layer of the glaze layer; the present application can visually achieve the effect of precipitation erosion on the surface of real stone.

[0065] The embodiment of the present application produces marble tiles with texture color and stone grain line texture close to real stone through the superposition of special digital inks and the combination of ink properties and glaze slurry properties after glazing. Compared with real stone, the stone grain line texture achieves a simulation effect of 0.1 mm fineness, giving the tiles a sense of age.

[0066] In the embodiment of the present application, the chemical components of the glaze, measured by mass percentage, include:

[0067] SiO2 50-54%, Al2O3 17-22%, CaO 5-8%, MgO 1-3%, Ka2O 4-6%, Na2O2-4%, ZnO5-8%, BaO 7-11%, SrO 2-4%.

[0068] Specifically, the wear resistance level of the glaze is level 4, and the wear resistance test data is 12,000 revolutions.

[0069] The embodiment of the present application adopts a glaze with high hardness and high transparency, which improves the transparency and hardness of the product after later polishing.

[0070] like Figure 1 As shown, the method for preparing marble tiles with stone luster also includes:

[0071] Step S300: Processing the ceramic body to which the glaze has been applied into a marble tile with a stone luster.

[0072] In the embodiment of the present application, the step S300 specifically includes:

[0073] Step S310, firing the ceramic body to which the glaze has been applied at a firing temperature of 1130-1230° C. and a firing time of 60-90 minutes to obtain a fired semi-finished product;

[0074] Step S320, glazing the fired semi-finished product using a polishing device;

[0075] Step S330: waxing the fired semi-finished product after glazing to obtain marble tiles with stone luster.

[0076] Specifically, the kiln firing temperature of the embodiment of the present application matches the glaze, SiO2 accounts for 50-54% of the glaze, Al2O3 accounts for 17-22%, the kiln ambient temperature is controlled at 1130-1230°C, and the kiln firing cycle is about 60-90 minutes, ensuring that the glaze and ink have a certain quality change time in different temperature ranges.

[0077] The firing process of the embodiment of the present application can form a good bond between the glaze and the ceramic body, enhancing the overall stability; polishing can remove tiny flaws on the glaze surface, making it smoother and brighter. The polished glaze has a stone-like luster, which improves the visual effect of the ceramic product; the polished glaze forms a hard protective layer, enhancing the wear resistance; the polished glaze is smoother and less likely to absorb dirt and dust. Waxing can form a protective film on the glaze surface to prevent the glaze from being worn and contaminated, and can maintain the gloss of the glaze.

[0078] In the embodiment of the present application, the step S320 specifically includes:

[0079] Step S321, using a 600-mesh elastic grinding block, an 800-mesh elastic grinding block and a resin brush on a first polishing device to perform a first glaze polishing;

[0080] In this step, the elastic grinding blocks of 600 mesh and 800 mesh have large particle fineness and high hardness, which will produce obvious fiber scratches when cutting the surface thickness of the glaze layer. The resin brush has high density and soft strength. The fiber scratches can be repaired during the brushing process.

[0081] Step S322, using an 800-mesh elastic grinding block on a second polishing device to perform a second glaze polishing;

[0082] In this step, a second glaze polishing is performed using an 800-mesh elastic grinding block to ensure that the product brick surface is evenly glazed.

[0083] Step S323, using a resin brush and an 800-mesh elastic grinding block on a third polishing device to perform a third glaze polishing;

[0084] In this step, the purpose of the third glaze polishing is to repair the surface fiber polishing marks of the product brick surface and enhance the grease gloss.

[0085] Step S324, using the elastic grinding block of 1000 mesh, the elastic grinding block of 1500 mesh, the elastic grinding block of 2000 mesh and the elastic grinding block of 3000 mesh on the fourth polishing equipment to perform the fourth glaze polishing.

[0086] In this step, the fourth glaze throwing is mainly to control the surface flexibility, gloss uniformity and glossiness.

[0087] Specifically, the embodiment of the present application adopts different superposition combinations of new elastic grinding blocks and special oily resin brushes. It includes 4 glaze polishing equipment. The combination of the first glaze polishing equipment is: 600 mesh elastic grinding block, 800 mesh elastic grinding block, pure resin brush; the combination of the second glaze polishing equipment is: 800 mesh elastic grinding block; the combination of the third glaze polishing equipment is: resin brush, 800 mesh elastic grinding block, used to increase the surface oiliness; the combination of the fourth glaze polishing equipment is: 1000 mesh elastic grinding block, 1500 mesh elastic grinding block, 2000 mesh elastic grinding block and 3000 mesh elastic grinding block.

[0088] The glaze polishing process of the present application is a rough polishing process using a superposition of an elastic bright polishing block and a resin brush, which achieves the effect of trimming and repairing the glaze polishing marks on the glaze surface, reducing fiber marks on the glaze surface, increasing the glaze surface flatness, and thus improving the product's light refractive index and increasing the product's transparency and clarity. The conventional glaze polishing process is to use an elastic polishing block to polish the glaze first, and then use a brush, which cannot trim and repair the glaze polishing marks on the glaze surface.

[0089] In one embodiment of the present application, the chemical components of the elastic grinding block and the resin brush, measured by mass percentage, both include:

[0090] Phenolic resin powder 35-45%, diamond powder 15-20%, corundum powder 5-10%, green silicon carbide powder 5-10%, zinc oxide powder 10-15%, cerium oxide powder 15-20%, titanium salt 4-6%, zinc stearate 2-4% 。

[0091] The characteristics of resin brush materials include: First, the resin elastic material is highly elastic and has strong resilience, and can return to its original shape after being subjected to force. Second, it has good wear resistance and can resist long-term physical wear. Third, it has good corrosion resistance and has good resistance to chemical substances such as acids and alkalis.

[0092] Conventional grinding blocks in the industry have many impurities of different hardness on the same plane. The grinding amount seems to be the same during use, but after zooming in, you will find that the fiber marks caused by the particles with high hardness and the particles with low hardness in the impurities are different in depth. Similarly, other particles account for a high proportion in the composition of the brush, resulting in a low proportion of resin, and different composition structures of the grinding block and the brush. As a result, the filling is incomplete during the later fine polishing and repair process. This causes light to scatter during the propagation of the brick surface, resulting in a clouding and whitening phenomenon. This situation results in poor product clarity and average transparency.

[0093] The present application uses abrasive blocks with high purity and few impurities, and the surface composition is basically the same. Moreover, the chemical composition of the abrasive blocks and brushes is the same. The fiber scratches produced during the grinding process are similar in depth, and the high-purity resin fiber brush fills and repairs the fiber scratches, while increasing the flatness of the surface layer, reducing the light scattering rate, and improving the penetration rate, achieving the effect of clear transparency, comfortable gloss, and smooth feel. Therefore, the present application can better fill and repair the surface of the product.

[0094] The embodiment of the present application controls the glazing effect during glazing, achieves high transparency of the product, can produce fine lines of stone grain and digital ink, and visually produces the concave and convex feeling of stone sedimentation presented from the inside. In addition, the surface touch of the marble tile after glazing is closer to the stone with a sense of age, which is qualitatively different from the touch of traditional full glazing. The marble tile provided by the present application is closer to the texture of the original ecological stone.

[0095] In the embodiment of the present application, the step S330 specifically includes: waxing the fired semi-finished product after glazing twice with the same wax water to obtain marble tiles with stone luster; wherein the wax water used for waxing includes: high permeability small molecular weight modified silicone, medium molecular weight modified silicone, large molecular weight modified silicone, environmentally friendly solvent oil and high-efficiency organic tin curing agent and other modified additives. The wax water commonly used in conventional high-gloss products in the industry is a combination of two different types of wax water: anti-fouling wax water and bright wax water.

[0096] Specifically, after waxing twice, the embodiment of the present application can maintain the moisture of the marble tile surface, thereby improving the durability of the product. In addition, after use and wear, there will be no defects of reflection and large gloss contrast in frequently worn parts. The main components of the wax water used for waxing include: high-permeability low-molecular-weight modified silicone, medium-molecular-weight modified silicone, high-molecular-weight modified silicone, environmentally friendly solvent oil, high-efficiency organic tin curing agent and other modified additives. Compared with conventional wax water, the wax water used in the embodiment of the present application has good permeability, better transparency, better anti-slip properties, anti-fouling properties and durability.

[0097] In a specific implementation, the ceramic powder is pressed into shape and dried to obtain a ceramic body; after the ceramic body is cooled, a high-temperature matte base glaze is applied, and then the ceramic body is sent to a drying kiln for drainage and temperature control. After 3D inkjet printing is performed on the dried ceramic body, the ceramic body is sent to a drying kiln again for drainage and temperature control. The ceramic body after inkjet printing is glazed in a high-pressure swing glaze cabinet and then fired, and the fired semi-finished product is polished, waxed, and edged to obtain marble tiles.

[0098] An embodiment of the present application also provides a marble tile, wherein the marble tile is prepared by the method for preparing a marble tile with stone luster as described above.

[0099] The marble tiles produced in this application have rich pattern details, colorful colors, beautiful and natural textures, and are closer to the original ecological stone.

[0100] The polishing and waxing method of the present application is suitable for products with different glossiness. Compared with the traditional polishing and waxing method, the products prepared by the method are one level higher in antifouling and permeability. The polishing method of the present application reduces light scattering, so the light permeability is better. The wax water used in the present application is better in antifouling than the traditional wax water, and the permeability is also better after the wax water is solidified. As shown in Table 1, Table 1 is a comparison of product performance after polishing using different polishing processes for products with different glossiness.

[0101] Table 1

[0102]

[0103]

[0104] In the embodiment of the present application, the thickness of the marble tile is 9 mm, and the glossiness of the marble tile is 65 to 70 degrees.

[0105] Specifically, the gloss of the product after glazing and before waxing reaches about 65 to 70 degrees, and it has high transparency and moisture, a surface hardness of 6-7, a wear resistance of 4, and good anti-fouling performance. That is, the gloss of the marble tile product itself provided in the embodiment of the present application is 65 to 70 degrees.

[0106] The marble tile produced in the embodiment of the present application has a thickness of 9 mm, which is thinner than conventional marble tiles, has a wider range of uses, and is closer to the original ecological stone. The 9 mm thick marble tile has a wider range of operability than the 12 mm thick marble tile, has more options, and improves the convenience of paving operations. In addition, the production of 9 mm marble tiles consumes fewer natural resources than the production of 12 mm marble tiles.

[0107] In addition, the present invention is a process of imitating the original stone in terms of surface effect. The hand feel, visual effect, surface concave corrosion points and stone lines can show the fine cracks caused by long-term squeezing of the stone. The gloss of existing tiles imitating original stone cannot reach 65-70 degrees, while the gloss of the present invention can reach 65-70 degrees. The present invention has an oily and moist gloss after glazing. The surface is not a mirror surface, and there are concave corrosion points, such as Figure 2 , Figure 3 and Figure 4 shown.

[0108] This application has achieved the following results:

[0109] First, the conventional marble tile products have incompatible touch and gloss, transparency and visual moist and greasy feeling on the surface. The marble tile prepared in the embodiment of the present application has clear transparency, touch close to real stone, and visually has moist and greasy feeling.

[0110] Second, the embodiment of the present application utilizes the superposition of two digital inks, matte carving digital ink and high-temperature matte white ink, to reproduce the fine stone grain texture that has grown naturally over thousands of years. The fineness of the stone grain line reaches 0.1mm, making the marble tiles more realistic.

[0111] Third, the 9 mm thick marble tiles produced in the embodiment of the present application reduce the consumption of raw materials and fuel.

[0112] Fourth, conventional 12 mm thick marble tiles are large in size and heavy in weight, and are difficult to lay and process. The 9 mm thick marble tiles of the embodiment of the present application solve the above problems.

[0113] Fifth, the preparation method of the present application is not only applicable to 9 mm thick marble tiles, but can also be used in other glazed products, thereby improving the clarity and transparency of other glazed products.

[0114] The present invention provides a method for preparing marble tiles with stone luster and marble tiles, the method for preparing marble tiles with stone luster comprising: inkjet printing a ceramic body to which a base glaze has been applied according to a pre-acquired stone texture pattern to obtain a pattern decoration layer, wherein the ink used in the inkjet printing comprises matte fine carving digital ink and high-temperature matte white ink; applying a top glaze on the pattern decoration layer so that the top glaze and the pattern decoration layer form an ink discharge phenomenon, and the ink discharge phenomenon is covered under the glaze layer formed by the top glaze; and processing the ceramic body to which the top glaze has been applied into a marble tile with stone luster. The present invention utilizes the superposition of two digital inks, matte fine carving digital ink and high-temperature matte white ink, and the combination of ink performance and glaze slurry performance after glazing to form an ink discharge phenomenon, and the ink discharge reaction occurs under the glaze layer, and then produces a surface depression from the inside to the outside after glazing, which can visually achieve the effect of precipitation erosion on the surface of real stone.

[0115] It should be understood that the application of the present invention is not limited to the above examples. For ordinary technicians in this field, improvements or changes can be made based on the above description. All these improvements and changes should fall within the scope of protection of the claims attached to the present invention.

Claims

1. A method for preparing marble tiles with stone luster, characterized in that: include: Inkjet printing is performed on the ceramic body to which the base glaze has been applied according to the pre-acquired stone texture pattern to obtain a pattern decoration layer, wherein the ink used in the inkjet printing includes matte fine carving digital ink and high-temperature matte white ink; Applying a top glaze on the pattern decoration layer, so that the top glaze and the pattern decoration layer form an ink drainage phenomenon, and the ink drainage phenomenon is covered under the glaze layer formed by the top glaze; The ceramic body to which the glaze has been applied is treated as a marble tile with a stone luster.

2. The method for preparing marble tiles with stone luster according to claim 1, characterized in that: The step of obtaining the stone texture pattern comprises: The surface of the target stone is scanned by a scanning device with a resolution of 3200 dpi to obtain an original scanned image, and the original scanned image is used as a stone texture pattern.

3. The method for preparing marble tiles with stone luster according to claim 1, characterized in that: Applying a top glaze on the pattern decoration layer so that the top glaze and the pattern decoration layer form an ink drainage phenomenon, and the ink drainage phenomenon is covered under the glaze layer formed by the top glaze, comprising: Using a swing-type pressure glaze spraying cabinet to apply a top glaze on the pattern decoration layer, so that the top glaze and the pattern decoration layer form an ink drainage phenomenon, and the ink drainage phenomenon is covered under the glaze layer formed by the top glaze; Among them, the pressure control of the swing pressure glaze spraying cabinet is 1-1.2MPa, the glazing specific gravity is 1.38-1.40, and the glazing amount is 130-190g / m 2 .

4. The method for preparing marble tiles with stone luster according to claim 1, characterized in that: The chemical components of the glaze, measured by mass percentage, include: SiO2 50-54%, Al2O3 17-22%, CaO 5-8%, MgO 1-3%, Ka2O 4-6%, Na2O2-4%, ZnO 5-8%, BaO 7-11%, SrO 2-4%.

5. The method for preparing marble tiles with stone luster according to claim 1, characterized in that: The glazed ceramic body is processed into a marble tile with a stone luster, including: The ceramic body to which the glaze has been applied is fired at a firing temperature of 1130 to 1230° C. and a firing time of 60 to 90 minutes to obtain a fired semi-finished product; Use polishing equipment to glaze the fired semi-finished products; The fired semi-finished product after glazing is waxed to obtain marble tiles with stone luster.

6. The method for preparing marble tiles with stone luster according to claim 5, characterized in that: Use polishing equipment to glaze the fired semi-finished products, including: The first glaze polishing is performed using a 600-mesh elastic grinding block, an 800-mesh elastic grinding block and a resin brush on the first polishing device; Use the 800-mesh elastic grinding block on the second polishing equipment to perform the second glaze polishing; Use the resin brush on the third polishing device and the 800-mesh elastic grinding block to perform the third glaze polishing; The fourth glaze polishing is performed using a 1000-mesh elastic grinding block, a 1500-mesh elastic grinding block, a 2000-mesh elastic grinding block and a 3000-mesh elastic grinding block on the fourth polishing equipment.

7. The method for preparing marble tiles with stone luster according to claim 6, characterized in that: The chemical components of the elastic grinding block and the resin brush, measured by mass percentage, include: Phenolic resin powder 35-45%, diamond powder 15-20%, corundum powder 5-10%, green silicon carbide powder 5-10%, zinc oxide powder 10-15%, cerium oxide powder 15-20%, titanium salt 4-6%, zinc stearate 2-4% 。 8. The method for preparing marble tiles with stone luster according to claim 5, characterized in that: Waxing the fired semi-finished product after glazing to obtain marble tiles with stone luster, including: The fired semi-finished product after glazing is waxed twice with the same wax water to obtain marble tiles with stone luster; Among them, the wax water used for waxing includes: high permeability small molecular weight modified silicone, medium molecular weight modified silicone, large molecular weight modified silicone, environmentally friendly solvent oil and high-efficiency organic tin curing agent.

9. A marble tile, characterized in that: The marble tile is prepared by the method for preparing a marble tile with stone luster as described in any one of claims 1 to 8.

10. The marble tile according to claim 9, characterized in that: The thickness of the marble tile is 9 mm, and the glossiness of the marble tile is 65-70 degrees.

Citation Information

Patent Citations

  • Wear-resistant antifouling marble tile preparation method and wear-resistant antifouling marble tile

    CN118546014A

  • Digital ink composition, ceramic tile with mold effect and preparation method of ceramic tile

    CN118755310A

  • Ceramic tile and method for the production thereof

    WO2010112228A1

  • Method for producing raised patterns on ceramic tiles

    WO2023187233A1